TECHNOMORALISM AND EPISTEMIC HEGEMONY: A CRITICAL DISCOURSE ANALYSIS OF ACADEMIC KNOWLEDGE IN INDONESIA AND THE UNITED STATES - Basuki, Amin (Rubikon : Journal of Transnational American Studies, 2026)
This article examines technomoralism as a hegemonic discursive regime through which scientific rationality and moral authority are integrated in contemporary academic knowledge production. While previous studies have addressed morality in science, technocratic governance, and epistemic inequality separately, limited research has examined how these dimensions intersect within a unified analytical framework, particularly in comparative contexts across the Global North and Global South. Addressing this gap, the study employs Critical Discourse Analysis (CDA) to analyze four academic articles from Indonesia and the United States. The analysis integrates Fairclough’s three-dimensional CDA framework with Gramsci’s theory of hegemony and Althusser’s concept of Ideological State Apparatuses to examine how moral–scientific discourse operates across textual features, discursive practices, and broader social structures. The findings reveal two dominant configurations of technomoralism. In Indonesia, technomoralism operates through technocratic nationalism, where technical expertise and statist morality legitimize state-centered governance and developmental agendas. In the United States, it takes the form of ethical liberalism, in which scientific rationality reinforces individual moral responsibility and institutional legitimacy. Despite contextual differences, both configurations naturalize the fusion of morality and science as common sense, thereby sustaining global epistemic hierarchies. This study contributes theoretically by conceptualizing technomoralism as an integrated discursive mechanism of epistemic hegemony, and empirically by demonstrating how academic discourse reproduces global knowledge inequalities.